The SmartVision navigation prototype for the blind - du Buf, J. M. H. (2011)
The goal of the project "SmartVision: active vision for the blind" is to develop a small and portable but intelligent and reliable system for assisting the blind and visually impaired while navigating autonomously, both outdoor and indoor. In this paper we present an overview of the prototype, design issues, and its different modules which integrate a GIS with GPS, Wi-Fi, RFID tags and computer vision. The prototype addresses global navigation by following known landmarks, local navigation with path tracking and obstacle avoidance, and object recognition. The system does not replace the white cane, but extends it beyond its reach. The user-friendly interface consists of a 4-button hand-held box, a vibration actuator in the handle of the cane, and speech synthesis. A future version may also employ active RFID tags for marking navigation landmarks, and speech recognition may complement speech synthesis.